No cerne da eficiência: uma análise comparativa sobre compiladores e seu desempenho - SILVA, Erick Vinícius Damasceno da (2024)
Since the 1950s, the exponential growth in demand for processing power has propelled the advancement of High-Performance Computing (HPC). In this scenario, compilers play a crucial role, surpassing the barriers of hardware elements and programming languages. These essential tools bear the vital responsibility of translating the high-level code crafted by programmers into the machine language understood by the computer. This study conducts a meticulous comparative analysis of compiler efficiency, utilizing energy consumption metrics across various domains of high-performance computing. The aim is to identify which compilers stand out in different areas of analysis, providing a solid foundation for the discerning selection of these tools, aligned with the specific nature of each task. The analysis indicates that, of the total energy consumed, GCC accounted for 33.23%, Clang for 36.01%, and ICC for 30.76%, respectively. Furthermore, ICC proved to be 7.43% more efficient than GCC, while Clang was 8.35% less efficient.